Polarizer Set
By designing a structure including a polarizing plate set with moderate thickness and introducing a phase difference layer, a polarizing mirror and an adhesive layer into its first polarizing plate, the problem of warping of liquid crystal panels in high temperature and high humidity environments is solved. Effective light leakage and display uniformity are achieved.
Patent Information
- Application Number
- CN201980077436.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-11-26
- Filing Date
- 2019-11-25
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2039-11-25
AI Technical Summary
The prior art is difficult to effectively suppress the warpage of the liquid crystal panel in a high temperature and high humidity environment, especially in a polarizer set containing thick constituent elements.
A polarizing plate set is designed, including a first polarizing plate with a thickness of 200 μm or more and 300 μm or less and a second polarizing plate with a thickness of 150 μm or less. The first polarizer has a phase difference layer of 100 μm or more, a polarizing mirror of 10 μm or less, and an adhesive layer, and is laminated on the liquid crystal cell by an adhesive layer.
It effectively suppresses the warpage of the liquid crystal panel in high-temperature and high-humidity environments, prevents light leakage and uneven display problems, and maintains the optical characteristics of the phase difference layer.
Smart Images

Figure CN113168041B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polarizing plate set. Background Art
[0002] Typically, a display panel having polarizers disposed on both sides of a display unit can be used in an image display device (e.g., a liquid crystal display device). The composition of each polarizer is different depending on the desired characteristics. Therefore, polarizers of different thicknesses can be disposed on both sides of the display unit. In the case of configuring polarizers of different thicknesses, the shrinkage stress of each polarizer is different, and therefore, warping of the liquid crystal panel may occur in a high temperature and high humidity environment. As a result, in an image display device equipped with these polarizers, problems of light leakage and uneven display may occur. As a method for suppressing the warping of a liquid crystal panel in a high temperature and high humidity environment, a method of laminating a protective film having a specific tensile modulus on a polarizer warped in a concave shape has been proposed (e.g., Patent Document 1). However, this technology is a technology involving thin polarizers, and there is a problem that warping cannot be fully suppressed in a polarizer equipped with a component element (e.g., a phase difference layer) having a certain degree of thickness and a large polarizer. Therefore, a polarizer group that can suppress the warping of a liquid crystal panel in a high temperature and high humidity environment even with a polarizer containing thick components and a large polarizer is required.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2018-72533 Summary of the invention
[0006] Problems to be solved by the invention
[0007] The present invention is made to solve the above-mentioned problems, and its main object is to provide a polarizing plate set capable of suppressing the warping of a liquid crystal panel in a high-temperature and high-humidity environment.
[0008] Solutions to the problem
[0009] The polarizing plate set of the present invention comprises: a first polarizing plate with a thickness of 200 μm or more and 300 μm or less arranged on one side of a liquid crystal cell, and a second polarizing plate with a thickness of 150 μm or less arranged on the other side of the liquid crystal cell. The first polarizing plate comprises: a phase difference layer with a thickness of 100 μm or more, a polarizer with a thickness of 10 μm or less arranged on one side of the phase difference layer, and an adhesive layer arranged on the other side of the phase difference layer. The first polarizing plate is laminated on the liquid crystal cell via the adhesive layer.
[0010] In one embodiment, the first polarizing plate further includes a protective layer, and the protective layer is laminated only on one surface of the polarizer.
[0011] In one embodiment, the adhesive layer has a creep value of 80 μm / h or more.
[0012] In one embodiment, the adhesive layer has a thickness of 10 μm to 40 μm.
[0013] In one embodiment, the first polarizing plate is disposed on the back side, and the second polarizing plate is disposed on the viewing side.
[0014] According to another aspect of the present invention, a liquid crystal panel is provided, which comprises: the polarizing plate group and a liquid crystal unit.
[0015] In one embodiment, the distance between the liquid crystal cell and the polarizer of the first polarizing plate is 120 μm to 190 μm.
[0016] Effects of the Invention
[0017] According to the present invention, a polarizing plate group capable of suppressing the warping of a liquid crystal panel in a high temperature and high humidity environment can be provided. The polarizing plate group of the present invention comprises: a first polarizing plate with a thickness of 200 μm or more and 300 μm or less arranged on one side of a liquid crystal unit, and a second polarizing plate with a thickness of 150 μm or less arranged on the other side of the liquid crystal unit. The first polarizing plate has: a phase difference layer with a thickness of 100 μm or more, a polarizer with a thickness of 10 μm or less arranged on one side of the phase difference layer, and an adhesive layer arranged on the other side of the phase difference layer, and the first polarizing plate is laminated on the liquid crystal unit via the adhesive layer. By having such a structure, the warping of the liquid crystal panel in a high temperature and high humidity environment can be suppressed, and as a result, the occurrence of light leakage and display unevenness in the liquid crystal display device can be prevented. In addition, the phase difference layer of the first polarizing plate used in the present invention has a thickness of 100 μm or more. Therefore, even if the liquid crystal panel is slightly warped in a high temperature and high humidity environment, the influence of the warping on the optical properties of the phase difference layer can be suppressed. As a result, the desired optical properties of the retardation layer can be well maintained, and even when placed in a high-temperature and high-humidity environment, it is possible to prevent the display properties of the liquid crystal display device from being degraded. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a schematic cross-sectional view of a liquid crystal panel including a polarizing plate set according to one embodiment of the present invention.
[0019] Explanation of symbols
[0020] 10 Liquid crystal unit
[0021] 21 1st polarizer
[0022] 22 Second polarizer
[0023] 31 Polarizer (1st polarizer)
[0024] 32 Phase difference layer
[0025] 33 Adhesive layer
[0026] 34 Protective layer
[0027] 35 Polarizer (2nd polarizer)
[0028] 36 Adhesive layer
[0029] 37 Protective layer
[0030] 100 LCD Panel DETAILED DESCRIPTION
[0031] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.
[0032] The definitions of terms and symbols in this specification are as follows.
[0033] (1) Refractive index (nx, ny, nz)
[0034] "nx" is the refractive index in the direction where the refractive index in the plane reaches the maximum (ie, the slow axis direction), "ny" is the refractive index in the direction orthogonal to the slow axis in the plane (ie, the fast axis direction), and "nz" is the refractive index in the thickness direction.
[0035] Unless otherwise specified, the “refractive index” of a film that develops birefringence after stretching means a value calculated from (nx+ny+nz) / 3.
[0036] (2) In-plane phase difference (Re)
[0037] "Re(550)" is the in-plane phase difference of the film measured at 23°C with light of a wavelength of 550nm. When the thickness of the film is set to d (nm), Re(550) can be calculated by the formula: Re = (nx-ny) × d. It should be noted that "Re(450)" is the in-plane phase difference of the film measured at 23°C with light of a wavelength of 450nm.
[0038] (3) Retardation in the thickness direction (Rth)
[0039] "Rth(550)" is the phase difference in the thickness direction of the film measured at 23°C with light of a wavelength of 550nm. When the thickness of the film is set to d (nm), Rth(550) can be calculated by the formula: Rth = (nx-nz) × d. It should be noted that "Rth(450)" is the phase difference in the thickness direction of the film measured at 23°C with light of a wavelength of 450nm.
[0040] (4) Nz coefficient
[0041] The Nz coefficient can be calculated by Nz=Rth / Re.
[0042] A. Overall composition of polarizer set
[0043] Figure 1 1 is a cross-sectional schematic diagram of a liquid crystal panel having a polarizing plate group according to an embodiment of the present invention. The liquid crystal panel 100 has a first polarizing plate 21 and a second polarizing plate 22 stacked on both sides of a liquid crystal cell 10. The thickness of the first polarizing plate is greater than 200 μm and less than 300 μm, and the thickness of the second polarizing plate is less than 150 μm. In the example shown in the figure, the first polarizing plate 21 has: a phase difference layer 32 with a thickness of more than 100 μm, a polarizer 31 with a thickness of less than 10 μm arranged on one side of the phase difference layer 32, an adhesive layer 33 arranged on the other side of the phase difference layer, and a protective layer 34 used as needed. The first polarizing plate 21 is stacked on the liquid crystal cell 10 via the adhesive layer 33. In addition, the second polarizing plate 22 has: a polarizer 35, a protective layer 37 arranged on one side of the polarizer 35, and an adhesive layer 36 arranged on the other side of the polarizer. The second polarizing plate 22 is stacked on the liquid crystal cell 10 via the adhesive layer 36. The polarizer 31 and the protective layer 34, and the polarizer 35 and the protective layer 37 can be laminated via any appropriate adhesive layer (not shown). In addition, the first polarizer 21 and the second polarizer 22 can also further have any appropriate other layers (not shown). As other layers, surface treatment layers and other protective layers can be listed. For the polarizer set of the present invention, representatively, the first polarizer can be arranged on the back side and the second polarizer can be arranged on the visible side.
[0044] The thickness of the first polarizer 21 is greater than 200 μm and less than 300 μm. The thickness of the phase difference layer 32 of the first polarizer 21 is greater than 100 μm. The thickness of the polarizer 31 of the first polarizer 21 (hereinafter also referred to as the first polarizer) is less than 10 μm. In one embodiment, it is preferred that the first polarizer 21 further has a protective layer 34. In this embodiment, it is preferred that the first polarizer 21 has a protective layer only on one side of the polarizer 31. By setting such a configuration, the thickness of the first polarizer 21 (more specifically, the distance from the first polarizer to the liquid crystal unit) can be prevented from becoming too thick, thereby suppressing the warping of the liquid crystal panel in a high temperature and high humidity environment.
[0045] In one embodiment, the distance between the polarizer 31 of the first polarizing plate and the liquid crystal unit 10 is preferably 120 μm to 190 μm, more preferably 140 μm to 190 μm, and further preferably 160 μm to 190 μm. By making the distance between the polarizer 31 and the liquid crystal unit 10 within the above range, the warping of the liquid crystal panel in a high temperature and high humidity environment can be suppressed. In this specification, the distance between the polarizer and the liquid crystal unit refers to the distance from the center of the polarizer (half the thickness of the polarizer) to the portion in contact with the liquid crystal unit. Specifically, Figure 1 Here, it refers to a value obtained by adding a value of 1 / 2 of the thickness of the polarizer 31 , the thickness of the phase difference layer 32 , and the thickness of the adhesive layer 33 .
[0046] The thickness of the second polarizing plate 22 is 150 μm or less. The thickness of the second polarizing plate 22 may be 150 μm or less, and may include any appropriate layer. The second polarizing plate 22 includes, for example, a polarizer 35, an adhesive layer 36 disposed on one side of the polarizer 35, and a protective layer 37 disposed on the other side of the polarizer 35. In this embodiment, the sum of the thickness of the polarizer 35, the thickness of the adhesive layer 36, and the thickness of the protective layer 37 may be 150 μm or less.
[0047] In one embodiment, the distance between the polarizer 35 of the second polarizer and the liquid crystal cell 10 is preferably 50 μm to 90 μm, more preferably 50 μm to 70 μm, and further preferably 55 μm to 65 μm. When the distance between the polarizer 35 of the second polarizer and the liquid crystal cell 10 is within the above range, the warping of the liquid crystal panel in a high temperature and high humidity environment can be further suppressed.
[0048] B. 1st polarizer
[0049] As described above, the thickness of the first polarizer 21 is greater than 200 μm and less than 300 μm, preferably 200 μm to 280 μm, and more preferably 220 μm to 250 μm. The first polarizer 21 has: a phase difference layer 32 with a thickness of more than 100 μm, a polarizer 31 with a thickness of less than 10 μm arranged on one side of the phase difference layer 32, and an adhesive layer 33 arranged on the other side of the phase difference layer 32. The first polarizer 21 is bonded to the liquid crystal unit via the adhesive layer 33. As described above, the thickness of the first polarizer is thicker than that of the second polarizer. In the polarizer group of the present invention, it is configured in a manner that the distance from the center of the polarizer of the first polarizer to the liquid crystal unit (specifically, the sum of half the value of the thickness of the polarizer, the thickness of the phase difference layer, and the thickness of the adhesive layer) does not become too thick. By setting it as such a configuration, the warping of the liquid crystal panel in a high temperature and high humidity environment can be suppressed.
[0050] In one embodiment, it is preferred that the first polarizer 21 further has a protective layer 34. By having a protective layer, the polarizer can be suitably protected. Preferably, the protective layer 34 is only laminated on one side of the polarizer. By laminating the protective layer on one side of the polarizer, more preferably on the side of the polarizer 31 where the phase difference layer 32 is not laminated, the polarizer can be suitably protected without increasing the thickness of the first polarizer. In practice, for the first polarizer 21, a diaphragm can be further laminated on the adhesive layer 33 until it is used in the manufacture of a liquid crystal panel. The following describes the various components of the first polarizer.
[0051] B-1. Polarizer
[0052] The thickness of the polarizer 31 is 10 μm or less, preferably 3 μm to 10 μm, and more preferably 3 μm to 8 μm. By using a thin polarizer, the thickness of the first polarizing plate 21 can be prevented from becoming too thick, and the distance from the polarizer to the liquid crystal cell can be shortened. Typically, the polarizer 31 is composed of a resin film containing a dichroic substance.
[0053] As the resin film, any appropriate resin film that can be used as a polarizer can be adopted. Typically, the resin film is a polyvinyl alcohol-based resin (hereinafter referred to as "PVA-based resin") film.
[0054] As the PVA resin forming the above-mentioned PVA resin film, any appropriate resin can be used. For example, polyvinyl alcohol and ethylene-vinyl alcohol copolymer can be listed. Polyvinyl alcohol can be obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymer is obtained by saponifying ethylene-vinyl acetate copolymer. The saponification degree of PVA resin is usually 85 mol% to 100 mol%, preferably 95.0 mol% to 99.95 mol%, and more preferably 99.0 mol% to 99.93 mol%. The saponification degree can be calculated according to JIS K 6726-1994. By using a PVA resin with such a saponification degree, a polarizer with excellent durability can be obtained. When the saponification degree is too high, there is a risk of gelation.
[0055] The average degree of polymerization of the PVA-based resin can be appropriately selected depending on the purpose. The average degree of polymerization is usually 1000 to 10000, preferably 1200 to 4500, and more preferably 1500 to 4300. The average degree of polymerization can be determined based on JIS K 6726-1994.
[0056] Examples of the dichroic substance contained in the resin film include iodine and organic dyes. These can be used alone or in combination of two or more. Iodine is preferably used.
[0057] The resin film may be a single-layer resin film or a laminate of two or more layers.
[0058] As a specific example of a polarizer composed of a single-layer resin film, there can be cited a polarizer formed by subjecting a PVA-type resin film to a dyeing treatment using iodine and a stretching treatment (representatively uniaxial stretching). The above-mentioned dyeing using iodine can be performed, for example, by immersing the PVA-type resin film in an iodine aqueous solution. The stretching ratio of the above-mentioned uniaxial stretching is preferably 3 to 7 times. Stretching can be performed after the dyeing treatment, or it can be performed while dyeing. In addition, dyeing can also be performed after stretching. The PVA-type resin film is subjected to swelling treatment, cross-linking treatment, cleaning treatment, drying treatment, etc. as needed. For example, by immersing the PVA-type resin film in water for washing before dyeing, not only can the dirt and anti-blocking agent on the surface of the PVA-type resin film be cleaned, but also the PVA-type resin film can be swelled to prevent uneven dyeing.
[0059] As a specific example of a polarizer obtained using a laminate, there can be cited a laminate using a resin substrate and a PVA-type resin layer (PVA-type resin film) laminated on the resin substrate, or a polarizer obtained using a laminate using a resin substrate and a PVA-type resin layer formed by coating on the resin substrate. The polarizer obtained using a laminate using a resin substrate and a PVA-type resin layer formed by coating on the resin substrate can be made by the following method: for example, a PVA-type resin solution is applied to a resin substrate, dried, and a PVA-type resin layer is formed on the resin substrate to obtain a laminate of the resin substrate and the PVA-type resin layer; the laminate is stretched and dyed to make the PVA-type resin layer into a polarizer. In the present embodiment, stretching typically includes immersing the laminate in a boric acid aqueous solution for stretching. In addition, stretching may further include stretching the laminate in a gas atmosphere at a high temperature (for example, above 95°C) before stretching in a boric acid aqueous solution as required. The obtained laminate of resin substrate / polarizer can be used directly (i.e., the resin substrate is made into a protective layer of polarizer), or the resin substrate can be peeled off from the laminate of resin substrate / polarizer, and any appropriate protective layer corresponding to the purpose can be laminated on the peeled surface for use. The details of the manufacturing method of such a polarizer are described in, for example, Japanese Patent Publication No. 2012-73580. The entire description of the publication can be cited as a reference in this specification.
[0060] The polarizer preferably exhibits absorption dichroism at any wavelength between 380 nm and 780 nm. The single transmittance of the polarizer is preferably between 43.0% and 46.0%, more preferably between 44.5% and 46.0%. The polarization degree of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and further preferably 99.9% or more.
[0061] B-2. Phase difference layer
[0062] The thickness of the phase difference layer 32 is greater than 100 μm, preferably 100 μm to 200 μm, more preferably 100 μm to 150 μm, and further preferably 110 μm to 150 μm. When the thickness of the phase difference layer is less than 100 μm, when the liquid crystal panel warps in a high temperature and high humidity environment, the phase difference layer will also warp. Therefore, the desired optical properties of the phase difference layer may sometimes be impaired. By making the thickness of the phase difference layer within the above range, the desired optical properties of the phase difference layer can be well maintained even when the liquid crystal panel is slightly warped in a high temperature and high humidity environment.
[0063] As the phase difference layer 32, any appropriate phase difference layer can be used as long as the phase difference layer has a thickness within the above range. Typically, the phase difference layer has a refractive index ellipsoid of nx>nz>ny. The Nz coefficient of the phase difference layer is preferably 0.1 to 0.9, more preferably 0.3 to 0.7, and further preferably 0.4 to 0.6.
[0064] As for the above-mentioned phase difference layer, as long as the above-mentioned characteristics can be obtained, it can be formed by any appropriate material. As a representative example, it is a stretched film of a polymer film. As the resin forming the polymer film, it is preferably a norbornene resin or a polycarbonate resin. It should be noted that the details of the resin forming the polymer film are recorded in, for example, Japanese Patent Publication No. 2014-010291. This record is used as a reference in this specification.
[0065] The above-mentioned norbornene resin is a resin obtained by polymerizing norbornene monomers as polymerization units. Examples of the norbornene monomers include norbornene and its alkyl and / or alkylidene-substituted products, such as 5-methyl-2-norbornene, 5-dimethyl-2-norbornene, 5-ethyl-2-norbornene, 5-butyl-2-norbornene, 5-ethylidene-2-norbornene, and their halogen- and other polar group-substituted products; dicyclopentadiene, 2,3-dihydrodicyclopentadiene, and the like; dimethyl-octahydronaphthalene, and its Alkyl and / or alkylidene substitutions, and polar group substitutions such as halogen, for example: 6-methyl-1,4:5,8-dimethyl-1,4,4a,5,6,7,8,8a-octahydronaphthalene, 6-ethyl-1,4:5,8-dimethyl-1,4,4a,5,6,7,8,8a-octahydronaphthalene, 6-ethyl-1,4:5,8-dimethyl-1,4,4a,5,6,7,8,8a-octahydronaphthalene, Naphthalene, 6-chloro-1,4:5,8-dimethyl-1,4,4a,5,6,7,8,8a-octahydronaphthalene, 6-cyano-1,4:5,8-dimethyl-1,4,4a,5,6,7,8,8a-octahydronaphthalene, 6-pyridyl-1,4:5,8-dimethyl-1,4,4a,5,6,7,8,8a-octahydronaphthalene, 6-methoxycarbonyl-1,4:5,8-dimethyl-1, 4,4a,5,6,7,8,8a-octahydronaphthalene, etc.; 3-4 polymers of cyclopentadiene, for example: 4,9:5,8-dimethyl-3a,4,4a,5,8,8a,9,9a-octahydro-1H-benzoindene, 4,11:5,10:6,9-trimethyl-3a,4,4a,5,5a,6,9,9a,10,10a,11,11a-dodecahydro-1H-cyclopentaanthracenes, etc. The above-mentioned norbornene resin can also be a copolymer of norbornene monomers and other monomers.
[0066] Various products are commercially available as the polynorbornene, and specific examples include "ZEONEX" and "ZEONOR" manufactured by Zeon Corporation, "Arton" manufactured by JSR Corporation, "TOPAS" manufactured by TICONA Corporation, and "APEL" manufactured by Mitsui Chemicals, Inc.
[0067] As the above-mentioned polycarbonate resin, aromatic polycarbonate is preferably used. Representatively, aromatic polycarbonate can be obtained by the reaction of carbonate precursors and aromatic dihydric phenol compounds. As the specific example of carbonate precursors, phosgene, dichloroformate, diphenyl carbonate, di-p-tolyl carbonate, phenyl carbonate, di-p-chlorophenyl carbonate, dinaphthyl carbonate etc. can be enumerated. Among these, phosgene and diphenyl carbonate are preferably used. Specific examples of aromatic dihydric phenol compounds include 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)butane, 2,2-bis(4-hydroxy-3,5-dipropylphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, etc. These can be used alone or in combination of two or more. Preferably, 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane are used. It is particularly preferred to use 2,2-bis(4-hydroxyphenyl)propane together with 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane.
[0068] The polymer film may contain any other appropriate thermoplastic resin. Other thermoplastic resins include: common plastics such as polyolefin resins, polyvinyl chloride resins, cellulose resins, styrene resins, acrylonitrile-butadiene-styrene resins, acrylonitrile-styrene resins, polymethyl methacrylate, polyvinyl acetate, polyvinylidene chloride resins; common engineering plastics such as polyamide resins, polyacetal resins, polycarbonate resins, modified polyphenylene ether resins, polybutylene terephthalate resins, polyethylene terephthalate resins; special engineering plastics such as polyphenylene sulfide resins, polysulfone resins, polyether sulfone resins, polyether ether ketone resins, polyarylate resins, liquid crystal resins, polyamide-imide resins, polyimide resins, polytetrafluoroethylene resins, etc.
[0069] As a method for preparing the above-mentioned stretched film, any appropriate method can be adopted. Representatively, a method of laminating a shrinkable film on one or both sides of the above-mentioned polymer film and performing heat stretching can be cited. The shrinkable film is used to impart a shrinkage force in a direction orthogonal to the stretching direction during heat stretching. As materials for the shrinkable film, for example, polyester, polystyrene, polyethylene, polypropylene, polyvinyl chloride, polyvinylidene chloride, etc. can be cited. From the perspective of excellent shrinkage uniformity and heat resistance, polypropylene film is preferably used.
[0070] As the above-mentioned stretching method, any appropriate stretching method can be adopted as long as it is possible to impart tension to the stretching direction of the above-mentioned polymer film and impart shrinkage force to the direction orthogonal to the stretching direction in the film surface. The stretching temperature is preferably above the glass transition temperature (Tg) of the above-mentioned polymer film. This is because the phase difference value of the obtained stretched film tends to become uniform, and the film is not easy to crystallize (cloudy). The stretching temperature is more preferably Tg+1℃~Tg+30℃ of the above-mentioned polymer film, further preferably Tg+2℃~Tg+20℃, particularly preferably Tg+3℃~Tg+15℃, and most preferably Tg+5℃~Tg+10℃. By setting the stretching temperature to such a range, uniform heating and stretching can be performed. In addition, it is preferred that the stretching temperature is constant in the film width direction. This is because a stretched film with good optical uniformity and a small deviation in the phase difference value can be produced.
[0071] The stretching ratio during the stretching can be set to any appropriate value. It is preferably 1.05 to 2.00 times, more preferably 1.10 to 1.50 times, further preferably 1.20 to 1.40 times, and particularly preferably 1.25 to 1.30 times. By setting the stretching ratio to such a range, a stretched film with less shrinkage in film width and excellent mechanical strength can be obtained.
[0072] In another embodiment, a film obtained by stretching a polymer film containing a polycarbonate resin and a styrene resin can be used. The details of such a phase difference film are described in, for example, Japanese Patent Application Publication No. 2005-31621. The entire description of the publication is incorporated herein by reference.
[0073] B-3. Adhesive layer
[0074] The adhesive layer 33 is formed on the side of the phase difference layer 32 that is not in contact with the polarizer 31. The creep value of the adhesive layer 33 is preferably 40 μm / h or more, more preferably 50 μm / h or more, further preferably 60 μm / h or more, and particularly preferably 80 μm / h or more. The adhesive layer having the creep value in the above range has flexibility. By forming such an adhesive layer, the shrinkage stress of the polarizer placed in a high temperature and high humidity environment can be alleviated. Therefore, the warping of the liquid crystal panel in a high temperature and high humidity environment can be better suppressed. In addition, the creep value of the adhesive layer is, for example, 200 μm / h or less.
[0075] The creep value of the adhesive layer can be measured as described below. An adhesive composition is applied to the protective layer of a polarizing plate including a protective layer and a polarizer to form an adhesive layer, and a polarizing plate (test piece) with an adhesive layer is prepared. The prepared test piece is cut into 10 mm wide × 50 mm long. The 10 mm wide × 10 mm long portion of the cut test piece is adhered to a stainless steel plate via the adhesive layer, and then treated in an autoclave (50°C, 5 atmospheres) for 15 minutes and then allowed to stand at room temperature for 1 hour. After standing, a load of 500 g (tensile load) is applied to the end of the test piece that is not adhered to the stainless steel plate at 23°C for 1 hour, and the offset (deformation) of the adhesive layer after the load is applied is measured using a laser creep tester, thereby determining the creep value of the adhesive layer.
[0076] The creep value of the adhesive layer can be adjusted by any appropriate method. For example, it can be adjusted according to the molecular weight of the base polymer in the adhesive forming the adhesive layer, the addition amount of the crosslinking agent in the adhesive, etc. More specifically, by using a polymer with a high molecular weight as the base polymer and / or increasing the addition amount of the crosslinking agent, the creep value of the adhesive layer can be reduced. In addition, by using a polymer with a low molecular weight as the base polymer and / or reducing the addition amount of the crosslinking agent, the creep value of the adhesive layer can be increased.
[0077] The thickness of the pressure-sensitive adhesive layer is preferably 1 μm to 50 μm, more preferably 10 μm to 40 μm. When the thickness of the pressure-sensitive adhesive layer is within the above range, the shrinkage stress of the polarizing plate can be well relaxed.
[0078] As the adhesive forming the adhesive layer, any appropriate adhesive can be used. As the adhesive, for example, acrylic adhesives, acrylic urethane adhesives, urethane adhesives, silicone adhesives, organic-inorganic hybrid adhesives, etc. can be cited. From the viewpoint of transparency and durability, acrylic adhesives are preferred.
[0079] Examples of acrylic adhesives include acrylic polymers using one or more (meth)acrylic acid alkyl esters as monomer components, that is, acrylic adhesives using a polymer (homopolymer or copolymer) having a structural unit derived from a (meth)acrylic acid alkyl ester as a base polymer. Specific examples of the alkyl (meth)acrylate include C1-C20 alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecanyl (meth)acrylate, octadecyl (meth)acrylate, nonadecanyl (meth)acrylate, and eicosyl (meth)acrylate. Among them, preferably used are (meth)acrylic acid alkyl esters having a linear or branched alkyl group with carbon numbers of 4 to 18. The content of the structural unit derived from the (meth)acrylic acid alkyl ester is preferably 60 parts by weight or more, more preferably 80 parts by weight or more, based on 100 parts by weight of the base polymer.
[0080] For the purpose of modifying cohesive force, heat resistance, crosslinking property, etc., the acrylic polymer may contain structural units derived from other monomer components copolymerizable with the alkyl (meth)acrylate, as required. Such monomer components include, for example, carboxyl group-containing monomers such as acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid; acid anhydride monomers such as maleic anhydride and itaconic anhydride; sulfonic acid group-containing monomers such as styrene sulfonic acid, allyl sulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, (meth)sulfopropyl acrylate, and (meth)acryloyloxynaphthalenesulfonic acid.
[0081] In one embodiment, as the above-mentioned monomer component, a hydroxyl-containing monomer is used. As a hydroxyl-containing monomer, for example, 2-hydroxyethyl (meth) acrylate, 3-hydroxypropyl (meth) acrylate, 4-hydroxybutyl (meth) acrylate, 6-hydroxyhexyl (meth) acrylate, 8-hydroxyoctyl (meth) acrylate, 10-hydroxydecyl (meth) acrylate, 12-hydroxylauryl (meth) acrylate, and methyl acrylate (4-hydroxymethylcyclohexyl) ester, etc., can be cited. In the case of using an isocyanate crosslinking agent as a crosslinking agent, from the viewpoint of efficiently ensuring the crosslinking point with the isocyanate group, among these, 4-hydroxybutyl acrylate is preferred. The content ratio of the structural unit from the hydroxyl-containing monomer is preferably 0.1 to 10 parts by weight relative to 100 parts by weight of the base polymer, and more preferably 0.5 to 2 parts by weight.
[0082] Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, peroxide crosslinking agents, melamine crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, Oxazoline crosslinking agents, aziridine crosslinking agents, amine crosslinking agents, etc. Among them, isocyanate crosslinking agents, epoxy crosslinking agents and / or peroxide crosslinking agents are preferably used. The crosslinking agent can be used alone or in combination of two or more.
[0083] As the above-mentioned isocyanate crosslinking agent, any appropriate crosslinking agent can be used. Examples of the isocyanate crosslinking agent include isocyanate monomers such as toluene diisocyanate, chlorophenylene diisocyanate, tetramethylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, and hydrogenated diphenylmethane diisocyanate; and isocyanate compounds obtained by adding polyols such as trimethylolpropane to these isocyanate monomers.
[0084] As the epoxy crosslinking agent, any appropriate crosslinking agent can be used. As the epoxy crosslinking agent, for example, an epoxy resin having two or more epoxy groups in the molecule can be used, and specifically, diglycidyl aniline, 1,3-bis(N,N-glycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidyl-m-xylene diamine, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, etc. can be cited.
[0085] As the above-mentioned peroxide crosslinking agent, any appropriate crosslinking agent can be used. Examples of the peroxide crosslinking agent include dibenzoyl peroxide, di(2-ethylhexyl) peroxydicarbonate, di(4-tert-butylcyclohexyl) peroxydicarbonate, di-sec-butyl peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-hexyl peroxypivalate, and tert-butyl peroxypivalate.
[0086] The amount of the crosslinking agent added is preferably 0.01 to 5 parts by weight, more preferably 0.02 to 3 parts by weight, further preferably 0.1 to 2.5 parts by weight, and particularly preferably 0.4 to 1 part by weight relative to 100 parts by weight of the base polymer. Within this range, an adhesive layer having an appropriate creep value can be formed.
[0087] In one embodiment, the adhesive forming the adhesive layer may further contain a silane coupling agent. As the silane coupling agent, for example, epoxy-containing silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; amino-containing silane coupling agents such as 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylene)propylamine, and N-phenyl-γ-aminopropyltrimethoxysilane; (meth)acrylic silane coupling agents; isocyanate-containing silane coupling agents, etc.
[0088] The amount of the silane coupling agent added is preferably 0.01 to 1 part by weight, more preferably 0.05 to 0.5 parts by weight, based on 100 parts by weight of the base polymer.
[0089] The adhesive may further contain any appropriate additives as required, such as tackifiers, plasticizers, pigments, dyes, fillers, anti-aging agents, conductive materials, ultraviolet absorbers, light stabilizers, release regulators, softeners, surfactants, flame retardants, etc.
[0090] B-4. Protective layer
[0091] Any appropriate resin film can be used as the protective layer 34. Examples of the material forming the resin film include: (meth) acrylic resin, cellulose resins such as cellulose diacetate and cellulose triacetate, cycloolefin resins such as norbornene resins, olefin resins such as polypropylene, ester resins such as polyethylene terephthalate resins, polyamide resins, polycarbonate resins, and copolymer resins thereof. It should be noted that "(meth) acrylic resin" refers to acrylic resin and / or methacrylic resin.
[0092] In one embodiment, as the (meth)acrylic resin, a (meth)acrylic resin having a glutarimide structure may be used. The (meth) acrylic resin having a glutarimide structure (hereinafter also referred to as glutarimide resin) is described in, for example, Japanese Patent Application Laid-Open No. 2006-309033, Japanese Patent Application Laid-Open No. 2006-317560, Japanese Patent Application Laid-Open No. 2006-328329, Japanese Patent Application Laid-Open No. 2006-328334, Japanese Patent Application Laid-Open No. 2006-337491, Japanese Patent Application Laid-Open No. 2006-337492, Japanese Patent Application Laid-Open No. 2006-337493, Japanese Patent Application Laid-Open No. 2006-337569, Japanese Patent Application Laid-Open No. 2007-009182, Japanese Patent Application Laid-Open No. 2009-161744, and Japanese Patent Application Laid-Open No. 2010-284840. These descriptions are incorporated herein by reference.
[0093] The moisture permeability of the protective layer 34 is preferably 1.0 g / m 2 / 24hr or less, more preferably 0.8g / m 2 / 24hr or less, more preferably 0.6g / m 2 / 24hr or less, particularly preferably 0.4g / m 2 When the moisture permeability of the protective layer is within such a range, the dimensional change of the protective layer in a high temperature and high humidity environment can be further suppressed, and as a result, the warping of the liquid crystal panel in the high temperature and high humidity environment can be further suppressed.
[0094] The thickness of the protective layer is typically 10 μm to 100 μm, preferably 20 μm to 40 μm. Typically, the protective layer is laminated on the polarizer via an adhesive layer (specifically, an adhesive layer, an adhesive layer). The adhesive layer is typically formed of a PVA-based adhesive or an active energy ray-curable adhesive. The adhesive layer is typically formed of an acrylic adhesive. The acrylic adhesive may be the same as or different from the adhesive constituting the above-mentioned adhesive layer.
[0095] C. Second polarizer
[0096] The thickness of the second polarizer 22 is 150 μm or less, preferably 80 μm to 140 μm, and more preferably 110 μm to 130 μm. The second polarizer 22 is a polarizer thinner than the first polarizer 21. The thickness of the second polarizer is 150 μm or less, and it includes any appropriate components. Representatively, the second polarizer 22 has: a polarizer 35, an adhesive layer 36, and a protective layer 37. The second polarizer 22 is attached to the liquid crystal unit via the adhesive layer 36. In practice, a diaphragm can be further laminated on the adhesive layer 36 before being used in the manufacture of a liquid crystal panel.
[0097] C-1. Polarizer
[0098] As the polarizer of the second polarizer, any appropriate polarizer can be used. A thin polarizer (for example, a thickness of 10 μm or less) disclosed in the above-mentioned first polarizer can be used, or a thick polarizer can be used. When a thick polarizer is used, the thickness of the polarizer is, for example, 10 μm to 35 μm, preferably 15 μm to 30 μm.
[0099] C-2. Adhesive layer
[0100] The adhesive layer can be formed using any appropriate adhesive. The adhesive layer can be formed using an adhesive (adhesive with a high creep value) used in the formation of the first polarizer, or can be formed using other adhesives (e.g., adhesives with a low creep value). By using an adhesive also used in the first polarizer to form the adhesive layer of the second polarizer, the shrinkage stress can be relaxed in the form of the entire liquid crystal panel, thereby further suppressing the warping of the liquid crystal panel in a high temperature and high humidity environment.
[0101] C-3. Protective layer
[0102] The protective layer may be formed of any appropriate film. For example, the film used for the protective layer of the first polarizer may be used.
[0103] D. LCD panel
[0104] The liquid crystal panel of the present invention comprises: the above-mentioned polarizer group and a liquid crystal unit. Typically, a first polarizer is laminated on one side of the liquid crystal unit via an adhesive layer, and a second polarizer is laminated on the other side of the liquid crystal unit. In one embodiment, the first polarizer can be arranged on the back side and the second polarizer can be arranged on the visible side.
[0105] As the driving mode of the above-mentioned liquid crystal unit, any appropriate driving mode can be adopted. As specific examples of the driving mode, there can be cited: STN (Super Twisted Nematic) mode, TN (Twisted Nematic) mode, IPS (In-Plane Switching) mode, VA (Vertical Aligned) mode, OCB (Optically Aligned Birefringence) mode, HAN (Hybrid Aligned Nematic) mode, ASM (Axially Symmetric Aligned Microcell) mode, ECB (Electrically Controlled Birefringence) mode, etc. In one embodiment, a liquid crystal unit of IPS mode can be appropriately adopted.
[0106] The thickness of the liquid crystal cell can be set to any appropriate value, for example, 0.7 mm or less, preferably 0.5 mm or less, and more preferably 0.5 mm to 0.2 mm.
[0107] E. Liquid crystal display device
[0108] The liquid crystal panel of the present invention can be applied to an image display device. In one embodiment, the liquid crystal panel can be configured in such a way that the first polarizer becomes the back side and the second polarizer becomes the visible side. In addition, when the second polarizer further has an anti-reflection layer, the anti-reflection layer can be configured on the visible side of the image display device in such a way that it becomes the visible side. As described above, in the polarizer group of the present invention, a thick phase difference layer can be used. Therefore, it can also be suitable for large-scale image display devices.
[0109] Example
[0110] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples. It should be noted that the measuring methods of the various properties are as follows.
[0111] (1) Creep value of adhesive layer
[0112] Adhesives A to C were applied to the protective layer of the polarizer obtained in Manufacturing Example 1 in such a manner that the thickness reached 20 μm to form an adhesive layer, and a polarizer with an adhesive layer was produced. The produced polarizer was cut into a width of 10 mm × a length of 50 mm as a test sample. The end of the cut test sample (width 10 mm × length 10 mm) was attached to a stainless steel plate via the adhesive layer, and after being treated in an autoclave at 50°C and 5 atmospheres for 15 minutes, it was placed at room temperature for 1 hour, and then the end on the opposite side of the end attached to the stainless steel plate was measured for the offset (deformation) of the adhesive layer when a load of 500 g (tensile load) was applied at 23°C for 1 hour, and it was used as the creep value of the adhesive layer (laser creep tester).
[0113] (2) Phase difference deviation
[0114] The in-plane phase difference deviation of the phase difference layer used for the first polarizing plate of Examples 1 to 4 and Comparative Examples 1 and 2 was measured using a phase difference measuring apparatus (manufactured by Oji Scientific Instruments Co., Ltd., product name: KOBRA-WPR).
[0115] The in-plane phase difference deviation of the phase difference layer was evaluated according to the following criteria.
[0116] ○(Good): 4nm or less
[0117] △ (pass): more than 4nm and less than 7nm
[0118] ×(Defective): More than 7nm
[0119] (3) Axis deviation
[0120] The in-plane axis deviation of the retardation layer used for the first polarizing plate of Examples 1 to 4 and Comparative Examples 1 and 2 was measured using a retardation measuring apparatus (manufactured by Oji Scientific Instruments Co., Ltd., product name: KOBRA-WPR).
[0121] The in-plane axis deviation of the phase difference layer was evaluated according to the following criteria.
[0122] ○(Good): 0.5° or less
[0123] △ (pass): more than 0.5° and less than 0.7°
[0124] ×(Defective): Exceeding 0.7°
[0125] <Synthesis Example 1> Synthesis of Adhesive A
[0126] 100 parts of butyl acrylate, 5 parts of acrylic acid, 0.075 parts of 2-hydroxyethyl acrylate and 0.3 parts of 2,2′-azobisisobutyronitrile were added together with ethyl acetate to a reaction vessel equipped with a condenser, a nitrogen inlet tube, a thermometer and a stirring device to prepare a solution. Next, nitrogen was bubbled into the solution while stirring, and the reaction was carried out at 60°C for 4 hours to obtain a solution containing an acrylic polymer with a weight average molecular weight of 2.2 million. Ethyl acetate was further added to the solution containing the acrylic polymer to obtain an acrylic polymer solution (A1) with a solid content concentration adjusted to 30%.
[0127] With respect to 100 parts of the solid content of the obtained acrylic polymer solution (A1), 0.6 parts of a crosslinking agent mainly composed of a compound having an isocyanate group (manufactured by Nippon Polyurethane Co., Ltd., trade name "Coronate L") and 0.075 parts of γ-glycidoxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "KMB-403") as a silane coupling agent were added in this order to prepare an adhesive A.
[0128] <Synthesis Example 2> Synthesis of Adhesive B
[0129] 99 parts of butyl acrylate, 1.0 part of 4-hydroxybutyl acrylate and 0.3 parts of 2,2′-azobisisobutyronitrile were added together with ethyl acetate into a reaction vessel equipped with a condenser, a nitrogen inlet tube, a thermometer and a stirring device, and reacted at 60° C. for 4 hours under a nitrogen flow. Next, ethyl acetate was added to the reaction solution to obtain a solution containing an acrylic polymer with a weight average molecular weight of 1.65 million (solid content concentration 30%).
[0130] 0.15 parts of dibenzoyl peroxide (manufactured by NOF Corporation, trade name: NYPER BO-Y), 0.08 parts of trimethylolpropane xylene diisocyanate (manufactured by Mitsui Takeda Chemical, Inc., trade name: Takenate D110N), and 0.2 parts of a silane coupling agent (manufactured by Soken Chemical Co., Ltd., trade name: A-100, acetoacetyl group-containing silane coupling agent) were added to the acrylic polymer solution based on 100 parts of the solid content of the obtained acrylic polymer solution to prepare an adhesive B.
[0131] <Synthesis Example 3> Synthesis of Adhesive Composition C
[0132] 81.9 parts of butyl acrylate, 13 parts of benzyl acrylate, 5 parts of acrylic acid, 0.1 parts of 4-hydroxybutyl acrylate and 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator were added together with 100 parts of ethyl acetate into a reaction vessel equipped with a condenser, a nitrogen inlet tube, a thermometer and a stirring device, and nitrogen was introduced while slowly stirring to perform nitrogen substitution. Next, the liquid temperature in the flask was maintained at around 55°C for 8 hours of polymerization reaction to prepare an acrylic polymer solution.
[0133] To 100 parts of the solid content of the obtained acrylic polymer solution, 0.45 parts of an isocyanate crosslinking agent (manufactured by Nippon Polyurethane Industries, Ltd., trade name: Coronate L, an adduct of trimethylolpropane and toluene diisocyanate), 0.1 parts of benzoyl peroxide (manufactured by NOF Corporation, trade name: NYPER BMT) and 0.1 parts of a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., trade name: KBM403) were added, thereby preparing an adhesive C.
[0134] <Manufacturing Example 1> Preparation of Polarizer Laminated Body 1
[0135] As the resin substrate, a long strip of amorphous isophthalic acid copolymer polyethylene terephthalate (IPA copolymer PET) film (thickness: 100 μm) with a water absorption of 0.75% and a Tg of 75° C. was used. One side of the substrate was subjected to corona treatment, and an aqueous solution containing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetic acid-modified PVA (polymerization degree 1200, acetoacetic acid modification degree 4.6%, saponification degree 99.0 mol% or more, manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER Z200") in a ratio of 9:1 was applied to the corona-treated surface and dried to form a PVA-based resin layer with a thickness of 11 μm, thereby producing a laminate.
[0136] The obtained laminate was subjected to free-end uniaxial stretching (auxiliary stretching in a gas atmosphere) in which the laminate was stretched to 2.0 times in the longitudinal direction (length direction) between rolls having different peripheral speeds in an oven at 120°C.
[0137] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution prepared by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 30° C. for 30 seconds (insolubilization treatment).
[0138] Next, the polarizing plate was immersed in a dye bath at a liquid temperature of 30° C. while adjusting the iodine concentration and immersion time so as to achieve a given transmittance. In this embodiment, the polarizing plate was immersed in an iodine aqueous solution containing 0.2 parts by weight of iodine and 1.5 parts by weight of potassium iodide per 100 parts by weight of water for 60 seconds (dyeing treatment).
[0139] Next, the sample was immersed in a crosslinking bath (boric acid aqueous solution prepared by mixing 3 parts by weight of potassium iodide with 100 parts by weight of water and mixing boric acid) at a liquid temperature of 30° C. for 30 seconds (crosslinking treatment).
[0140] Then, the laminate was immersed in an aqueous boric acid solution (an aqueous solution obtained by adding 4 parts by weight of boric acid to 100 parts by weight of water and potassium iodide) at a liquid temperature of 70°C, and was uniaxially stretched (stretched in aqueous solution) between rollers with different circumferential speeds along the longitudinal direction (length direction) so that the total stretching ratio reached 5.5 times.
[0141] Then, the laminated body was immersed in a cleaning bath (an aqueous solution prepared by mixing 4 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 30° C. (cleaning treatment).
[0142] Next, a PVA resin aqueous solution (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER (registered trademark) Z-200", resin concentration: 3 wt%) is applied to the surface of the PVA resin layer (polarizer) of the laminate, and a methacrylic resin film (thickness: 25 μm, a film containing a (meth) acrylic resin having a glutarimide structure) constituting a protective layer is adhered thereto, and heated in an oven maintained at 60°C for 5 minutes. Then, the resin substrate is peeled off from the PVA resin layer. In this way, a polarizer laminate (a polarizing plate having a protective layer / polarizer structure) is obtained. It should be noted that the thickness of the polarizer is 5 μm and the single body transmittance is 42.3%.
[0143] <Manufacturing Example 2> Preparation of Polarizer Laminated Body 2
[0144] A 60 μm thick polyvinyl alcohol (average degree of polymerization 2400, saponification degree 99.9 mol%) film was immersed in 30°C warm water for 60 seconds to swell. Next, it was immersed in an iodine / potassium iodide aqueous solution (weight ratio: 0.5 / 8, concentration: 0.3 wt%) and dyed while stretching the film to 3.5 times. Then, it was stretched in a 65°C borate aqueous solution until the total stretch ratio reached 6 times. After stretching, it was dried in a 40°C oven for 3 minutes to obtain a polarizer.
[0145] Next, a first transparent protective film (TAC film, thickness: 40 μm) and a second transparent protective film (acrylic resin film, thickness: 30 μm) were bonded to both sides of the polarizer via an adhesive layer to prepare a polarizer laminate. The polarizer had a thickness of 22 μm and a single-unit transmittance of 41.5%.
[0146] <Production Example 3> Preparation of Phase Difference Layer 1
[0147] On both sides of a polymer film (JSR Corporation, trade name "ARTON FLZU130D0") having a thickness of 130 μm and comprising a resin obtained by hydrogenating a ring-opening polymer of a norbornene-based monomer, a shrinkable film (C) (Toray Corporation, product name: TORAYFAN) was attached via an acrylic adhesive layer (thickness 15 μm). Next, the film was stretched to 1.42 times in an air circulation constant temperature oven at 146°C ± 1°C while maintaining the film in the longitudinal direction using a roll stretcher. The obtained retardation film had a thickness of 138 μm, Re (550) = 270 nm, and Nz = 0.5. This retardation film was used as retardation layer 1.
[0148] <Production Example 4> Preparation of Phase Difference Layer 2
[0149] 10 kg of polyarylate was dissolved in 73 kg of toluene to prepare a coating liquid. Then, the coating liquid was directly applied to a shrinkable film (longitudinally uniaxially stretched polypropylene film, manufactured by Tokyo Ink Co., Ltd., trade name "Noblen"), and the coating was dried at a drying temperature of 60°C for 5 minutes and at 80°C for 5 minutes to form a shrinkable film / birefringent layer laminate. Using a synchronous biaxial stretching machine, the obtained laminate was stretched at a stretching temperature of 155°C with a shrinkage ratio of 0.70 times in the MD direction and 1.15 times in the TD direction, thereby forming a phase difference film on the shrinkable film. Next, the phase difference film was peeled off from the shrinkable film. The thickness of the phase difference film is 17.0 μm, Re (550) = 300 nm, Nz = 0.5. The phase difference film is used as the phase difference layer 2.
[0150] [Example 1]
[0151] An acrylic adhesive was applied to the polarizer of the polarizer laminate obtained in Production Example 1 to a thickness of 20 μm, and a phase difference layer 1 was laminated. Next, an adhesive B was applied to the side of the laminated phase difference layer 1 that was not in contact with the polarizer to a thickness of 20 μm to form an adhesive layer, thereby obtaining a first polarizing plate.
[0152] Separately, the adhesive A was applied to the polarizer of the polarizer laminate obtained in Production Example 1 so as to have a thickness of 23 μm to form an adhesive layer, thereby obtaining a second polarizing plate.
[0153] Various evaluations were performed using the polarizing plate set consisting of the obtained first polarizing plate and second polarizing plate.
[0154] [Example 2]
[0155] A first polarizing plate was obtained in the same manner as in Example 1 except that the adhesive A was used instead of the adhesive B to form an adhesive layer (thickness 23 μm).
[0156] The adhesive A was applied to the polarizer of the polarizer laminate obtained in Production Example 2 so as to have a thickness of 20 μm to form an adhesive layer, thereby obtaining a second polarizing plate.
[0157] Various evaluations were performed using the polarizing plate set consisting of the obtained first polarizing plate and second polarizing plate.
[0158] [Example 3]
[0159] A second polarizing plate was obtained in the same manner as in Example 2 except that the adhesive B was used instead of the adhesive A to form the adhesive layer using the second polarizing plate.
[0160] A polarizing plate set was obtained in the same manner as in Example 2 except that the obtained second polarizing plate was used. Various evaluations were performed using this polarizing plate set.
[0161] [Example 4]
[0162] A second polarizing plate was obtained in the same manner as in Example 2 except that the pressure-sensitive adhesive layer A was replaced with the pressure-sensitive adhesive C to form the pressure-sensitive adhesive layer of the second polarizing plate.
[0163] A polarizing plate set was obtained in the same manner as in Example 2 except that the obtained second polarizing plate was used. Various evaluations were performed using this polarizing plate set.
[0164] (Comparative Example 1)
[0165] A polarizing plate set was obtained in the same manner as in Example 1 except that the phase difference layer 2 was used instead of the phase difference layer 1. Various evaluations were performed using this polarizing plate set.
[0166] (Comparative Example 2)
[0167] A first polarizing plate was obtained in the same manner as in Example 1 except that the polarizer laminate obtained in Production Example 2 was used.
[0168] A second polarizing plate was obtained in the same manner as in Example 1 except that the polarizer laminate obtained in Production Example 2 was used.
[0169] Various evaluations were performed using the polarizing plate set consisting of the obtained first polarizing plate and second polarizing plate.
[0170] <Evaluation>
[0171] The polarizing plate sets of Examples 1 to 4 and Comparative Examples 1 to 2 were bonded to each other via an adhesive layer so as to sandwich a glass plate (thickness: 0.55 mm) to obtain a laminate. The following evaluations were performed using the obtained laminate. The results are shown in Table 1.
[0172] 1. Uneven appearance and light leakage
[0173] The obtained laminate was placed on a backlight, and the presence or absence of unevenness at the four corners and light leakage were confirmed and evaluated based on the following criteria.
[0174] ◎(Best): No unevenness or light leakage in the four corners
[0175] ○ (Good): Unevenness or light leakage at the four corners
[0176] × (bad): unevenness and light leakage at the four corners
[0177] 2. Warpage
[0178] The focal lengths of the four corners of the second polarizer (visible side polarizer) of the obtained laminate were measured using a planar biaxial measuring instrument (manufactured by Mitutoyo Co., Ltd., product name: Quick Vision Apex). Next, the laminate was placed under reliability test conditions (85°C) for 24 hours, and the focal lengths of the four corners of the second polarizer side (visible side polarizer) were measured in the same manner. The difference in focal length of each corner before and after the reliability test was calculated, and the average value of the four corners was taken as the warping amount of each polarizer group. Each warping amount was evaluated according to the following criteria. It should be noted that, respectively, "+" in Table 1 indicates that the laminate is curled in a convex state downward (i.e., the back side), and "-" indicates that the laminate is curled in a convex state upward (i.e., the visible side).
[0179] ◎(Best): 0mm or more and 0.5mm or less
[0180] ○ (good): more than 0.5 mm and less than 1.0 mm
[0181] △ (pass): more than 1.0 mm and less than 2.0 mm
[0182] ×(Defective): More than 2.0 mm
[0183]
[0184] As is clear from Table 1, the polarizing plate sets of Examples 1 to 4 suppressed warping even when placed in a high temperature and high humidity environment of the laminate. In these polarizing plate sets, appearance unevenness and light leakage were also small. In addition, the optical properties of the phase difference layer were well maintained.
[0185] Industrial Applicability
[0186] The polarizing plate set of the present invention can be suitably used in a liquid crystal display device.
Claims
1. A polarizer set, comprising: A first polarizing plate having a thickness of 200 μm or more and 300 μm or less and disposed on one side of the liquid crystal cell, and a second polarizing plate having a thickness of 150 μm or less and disposed on the other surface of the liquid crystal cell, in, The first polarizing plate has: A retardation layer having a thickness of 100 μm or more, a polarizer having a thickness of 10 μm or less and disposed on one side of the phase difference layer; and an adhesive layer disposed on the other side of the phase difference layer, The first polarizing plate is laminated on the liquid crystal cell via the adhesive layer. The phase difference layer is a stretched film using a norbornene-based resin or a polycarbonate-based resin film, and the creep value of the adhesive layer is 80 μm / h or more.
2. The polarizer set according to claim 1, wherein: The first polarizer further comprises a protective layer, The protective layer is laminated on only one side of the polarizer.
3. The polarizing plate set according to claim 1 or 2, wherein: The thickness of the adhesive layer is 10 μm to 40 μm.
4. The polarizing plate set according to claim 1 or 2, wherein: The first polarizing plate is arranged on the back side, and the second polarizing plate is arranged on the viewing side.
5. A liquid crystal panel comprising: The polarizing plate set according to any one of claims 1 to 4, and Liquid crystal cell.
6. The liquid crystal panel according to claim 5, wherein: The distance between the liquid crystal unit and the polarizer of the first polarizing plate is 160 μm to 190 μm.
Citation Information
Patent Citations
Optical film, polarizing optical film and image display apparatus
JP2005031621A
Method for manufacturing film for optics
JP2006309033A
Polarizer protective film, and polarizing plate using the same
JP2006317560A
Base material for surface-protective film and surface-protective film
JP2006328329A
Resin composition, optical film and polarizer protection film using the same
JP2006328334A